THE MANAGERIAL ROLE OF THE MADRASAH HEAD IN REALIZING ATTITUDE OF TEACHERS' CONCERN FOR INSTITUTIONS - Abbas, Athaur Rahman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and understand the leadership role of the madrasa head in growing and realizing a sense or attitude of caring for the teacher towards the institution he leads, knowing and understanding how sensitive and caring the teacher is towards the institution that shelters him, and how much the teacher's concern for his institution increases after the madrasa principal implements several ways. This research uses a qualitative approach with a case study type. The researcher seeks to investigate phenomena in real-life contexts by utilizing several sources closely related to formal educational institutions. In this qualitative research, the researcher acts as the main instrument (the instrument of choice in naturalistic inquiry is the human) and the data collector. At the same time, the data in this study were in the form of words, behaviour, documents and others regarding changes in the conduct of educators, educational staff and other staff, which were obtained using observation, interview and documentation data collection techniques. The results of this study are in the form of main findings, namely: 1) Not forcing teachers to work beyond their abilities. 2) Empathize when the teacher has difficulties in carrying out their obligations. 3) Forgive teacher/employee mistakes. 4) Giving rewards or bonuses to teachers who have carried out their obligations properly. 5) Have a high sense of empathy for teachers who are experiencing a disaster. 6) Be open to subordinates.